Elucidation of the Differences in Cinobufotalin’s Pharmacokinetics Between Normal and Diethylnitrosamine-Injured Rats: The Role of P-Glycoprotein - Zhang, Xiaojing; Liu, Tong; Zhang, Yidan; Liu, Fanye; Li, Haiying; Fang, Dong; Wang, Chaojie; Sun, Hua; Xie, Songqiang (Frontiers in Pharmacology, 2019)
Cinobufotalin is one of the major anti-tumor components isolated from toad venom and has been used in the clinical therapy of hepatocellular carcinoma (HCC), known as Cinobufacini injection. However, the pharmacokinetic (PK) behaviors of cinobufotalin in vivo with hepatocellular carcinoma are still unknown. Hence, we have established a HCC model in Sprague Dawley (SD) rats induced by diethylnitrosamine (DEN), named as DEN-injured rats. Then, we developed and validated a sensitive and rapid ultra-performance liquid chromatography-tandem mass spectrometric (UPLC-MS/MS) method to quantify cinobufotalin in rat plasma. This UPLC-MS/MS method was successfully used to characterize the PK behaviors of cinobufotalin in normal and DEN-injured rats after intravenous (i.v.) injection at a dosage of 2.5 mg/kg. Cinobufotalin pharmacokinetics was well described by the two-compartment pharmacokinetic model and the PK parameters were calculated using WinNonlin 3.3 software. The transfer rate constant of cinobufotalin from the central compartment to the peripheral compartment (k12) in DEN-injured rats was significantly greater than that in normal rats (p < 0.01), accompanied by the shorter half-life for the distribution phase (t1/2α). Additionally, the elimination rate constant (K10) and clearance (CL) values in DEN-injured rats were significantly higher than that in normal rats (p < 0.05 for K10 and p < 0.001 for CL, respectively). Therefore, the values of areas under concentration - time curve (AUC) and the liver concentration of cinobufotalin in DEN-injured rats was obviously lower than that in normal rats (p < 0.001 and p < 0.01, respectively). This indicated that the PK behaviors of cinobufotalin will be altered in rats with HCC. In addition, P-glycoprotein (P-gp) has shown higher expression in live tissues of DEN-injured rats. Furthermore, cinobufotalin was identified as the substrate of P-gp using MDCK II and MDCK-MDR1 cell models for the first time. Consequently, P-gp will play an important role in the disposition of cinobufotalin in vivo, which provided a new combination therapy for the clinical treatment of HCC.